2016
DOI: 10.1103/physrevlett.116.166601
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Chiral Magnetic Effect in a Weyl Semimetal with a Topological Defect

Abstract: We propose a torsional response raised by lattice dislocation in Weyl semimetals akin to chiral magnetic effect; i.e. a fictitious magnetic field arising from screw or edge dislocation induces charge current. We demonstrate that, in sharp contrast to the usual chiral magnetic effect which vanishes in real solid state materials, the torsional chiral magnetic effect exists even for realistic lattice models, which implies the experimental detection of the effect via SQUID or nonlocal resistivity measurements in W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
103
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 77 publications
3
103
1
Order By: Relevance
“…Examples include d x 2 −y 2 cuprates and odd-parity p-wave cases. In view of similar proposals for pseudo-magnetic fields in Weyl semi-metals [10][11][12][13][14][15]28], such effects are also likely to occur in more complicated 3D systems.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Examples include d x 2 −y 2 cuprates and odd-parity p-wave cases. In view of similar proposals for pseudo-magnetic fields in Weyl semi-metals [10][11][12][13][14][15]28], such effects are also likely to occur in more complicated 3D systems.…”
mentioning
confidence: 89%
“…In contrast to genuine magnetic fields in a SC, there are no induced currents and no screening associated with the Meissner effect. Our work is motivated by interesting developments in graphene [8] where strain-induced pseudo-magnetic fields lead to Landau quantization and quantum oscillations, which were already observed in experiment [9], and more recent proposals in the context of Dirac and Weyl semimetals [10][11][12][13][14][15].A possible experimental setup is shown in Fig. 1.…”
mentioning
confidence: 99%
“…In graphene, for instance, the effect of curvature is famously analogous to a pseudomagnetic field [21] that can be quite large and is known to generate pronounced Landau levels observed in the tunneling spectroscopy [22]. Recent theoretical work [23][24][25][26][27] showed that similar effects can be anticipated in three-dimensional Dirac and Weyl semimetals, although the estimated field strengths in the geometries that have been considered are rather small (below 1 Tesla in Ref. [26]).…”
mentioning
confidence: 99%
“…(For such a spatial separation of counterpropagating particle currents in the normal state, see Refs. [53][54][55]). …”
mentioning
confidence: 99%